Effect of Integrated Use of Inorganic and Organic Materials on the Distribution of Different Forms of Nitrogen in Soil and their Influence on Sugarcane Yield and Nutrient Uptake - and A.P. Singh, U.N. Umesh, Vipin Kumar, R.K. Prasad, K.D.N. Singh (Journal of the Indian Society of Soil Science, 2014)
A study was undertaken to evaluate the effect of fertilizers and organic manures (biogas slurry, green manure, sulphitation pressmud and sugarcane trash) on the amount and distribution of nitrogen (N) fractions in soil. After 17th crop cycles of sugarcane based cropping system, application of fertilizers alone and in combination with organic manures significantly increased all the forms of N except NO3--N over control (N50P100K100). Among the various N fractions non-hydrolysable N was the dominant N fraction. The highest values of these fractions were found in T4 (100% NPK + 20 t ha-1 biogas slurry). The relative contents of these fractions were in order : non-hydrolysable N > amino acid-N > unidentified-N > hydrolysable NH4+-N > exchangeable NH4+-N > hexoseamine-N > NO3–-N. All the fractions except NO3–-N were in dynamic equilibrium as indicated by significant and positive correlation (r = 0.861** to 0.977**) among them. The per cent distribution of soil N into different N fractions varied from 2.15 to 3.24 per cent as NO3–-N, 11.4 to 15.6 per cent exchangeable NH4+-N, 4.54 to 5.37 per cent hexoseamine-N, 18.6 to 20.8 per cent amino acid-N and 13.3 to 14.3 per cent in unidentified form of N. Correlation studies between plant parameters of sugarcane and soil N fractions indicated that the yield of sugarcane as well as sugar yield and uptake of N, P, K, S and Zn by sugarcane were significantly and positively correlated with all N fractions except NO3–-N.